2016
DOI: 10.1007/s00253-016-7718-y
|View full text |Cite
|
Sign up to set email alerts
|

Insect antimicrobial peptides: potential tools for the prevention of skin cancer

Abstract: Antimicrobial peptides/proteins (AMPs) are biologically active molecules with diverse structural properties that are produced by mammals, plants, insects, ticks, and microorganisms. They have a range of antibacterial, antifungal, antiviral, and even anticancer activities, and their biological properties could therefore be exploited for therapeutic and prophylactic applications. Cancer and cancer drug resistance are significant current health challenges, so the development of innovative cancer drugs with minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 100 publications
0
38
0
3
Order By: Relevance
“…We recently isolated a 15-mer peptide from the American cockroach, showed that it has antimicrobial activity, and designated it Periplanetasin-2 (Peri-2, YPCKLNLKLGKVPFH). Based on previous findings that antimicrobial peptides exhibit various biological effects against mammalian cells [23], we herein assessed whether Peri-2 could inhibit the epithelial damage and inflammation induced by C. difficile toxin A. Our results revealed that Peri-2 can inhibit toxin A-induced cellular toxicity in HT29 cells and ameliorate toxin A-induced enteritis in mice.…”
Section: Introductionmentioning
confidence: 94%
“…We recently isolated a 15-mer peptide from the American cockroach, showed that it has antimicrobial activity, and designated it Periplanetasin-2 (Peri-2, YPCKLNLKLGKVPFH). Based on previous findings that antimicrobial peptides exhibit various biological effects against mammalian cells [23], we herein assessed whether Peri-2 could inhibit the epithelial damage and inflammation induced by C. difficile toxin A. Our results revealed that Peri-2 can inhibit toxin A-induced cellular toxicity in HT29 cells and ameliorate toxin A-induced enteritis in mice.…”
Section: Introductionmentioning
confidence: 94%
“…Skin cancer is a widespread cancer, as skin serves as the first line of defence against heat, sunlight, injury, and infection [121]. Several in vivo studies have revealed that pomegranate possess anti-skin tumor promoting properties in various animal models [122,123].…”
Section: Pomegranate and Skin Cancermentioning
confidence: 99%
“…Система врожденного иммунитета животных обеспечивает немедленную защиту организма в ответ на внедрение патогена благодаря большому числу молекулярных факторов, реализующих рекогносцировочные и эффекторные механизмы ее функционирования. Наряду с множеством белковых факторов врожденного иммунитета, таких как компоненты системы комплемента, лизоцим, лактоферрин, цитокины и др., особую роль в защите организма от инфекций играют эндогенные антимикробные пептиды, продуцируемые позвоночными [28] и беспозвоночными [23] животными, растениями [72], грибами и бактерия ми. В отличие от многих классических антибиотиков, являющихся продуктами вторичного метаболизма, подавляющее большинство АМП синтезируются непосредственно на рибосомах.…”
Section: общая характеристика свойства и структура ампunclassified